RELIABILITY ASSESSMENT OF HORIZONTAL WELL SYSTEM SUBJECTED TO BURST AND COLLAPSE PRESSURE - ABDUL HALIM, AMIRAH HUSNA (2019)
Various drilling methods have been introduced since 1980s, where horizontal well drilling has become one of the popular methods in drilling the oil and gas wells. In the horizontal well drilling, a well system consists of casing and tubing are the backbones for drilling, production and workover operations.